(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Anthroponyms in English and Uzbek will be analyzed in our article. Linguistics of modern Uzbekistan is characterized by an in-depth study of foreign languages both in theoretical and practical terms, as well as the development of new directions aimed at the study of language about the study of thought processes, place and role of a person always a world that is becoming more complex, the peculiarities of human language behavior within different social groups (linguistic pragmatics).